A Protocol of a Pilot Experimental Study Using Social Network Interventions to Examine the Social Contagion of Attitudes Towards Childhood Vaccination in Parental Social Networks. Issue 1 (17th November 2022) - Christodoulou, Andria; Konstantinou, Pinelopi; Antoniou, Zinonas; Boda, Zsofia; Iasonides, Michalis; Kyprianidou, Maria; McHugh, Louise; Michaelides, Michalis P.; Karekla, Maria; Kassianos, Angelos P.
Increasing vaccination hesitancy that burdens global health and safety can be attributed to multiple reasons. Individuals' social environment seems to be the catalyst for vaccination hesitancy perpetuation, thus it is important to examine the influence of different social network mechanisms in vaccination attitudes' contagion. The proposed pilot experiment will examine the social contagion of childhood vaccination attitudes within a parental community using social network interventions. By identifying centrally-located people or groups of like-minded individuals from a parents' community, we will examine whether the position of a person within a social group can have a greater impact in spreading positive vaccination messages to other community members. Parents will be recruited from social media and will be randomly assigned into three groups. Firstly, each group will participate in an online game to map their social networks and identify members with certain network position, who will then receive a short training about valid vaccination information provisions. All groups' members will participate in daily vaccination discussion groups for one week, where the selected members will spread positive vaccination attitudes to others. We hypothesize that centrally located individuals and like-minded group of people will more likely cause a change on the childhood-vaccination attitudes and will sustain a long-term change at 3 months follow-up, compared to randomly located people.